Iron, Folate and Vitamin B12 Status of Children and Adolescents: Single Center Study in the Aegean Region - Ayfer Çolak; Merve Zeytinli Akşit; Neşe Şimşek; Pınar Bilgi; Murat Anıl (Galenos Publishing House, 2019)
INTRODUCTION: Although anemia is common in children, there isn't much study related with this issue. In this study, we aimed to investigate iron, folate and vitamin B12 status in children and adolescents in a single center study in the aegean region of our country. METHODS: We evaluated the children without chronic disease who were admitted to our hospital between 2008-2016 (n=7310), retrospectively. Ferritin, iron and iron binding capacity were measured by Olympus 2700 analyzer. Folate and vitamin B12 were measured by Immulite 2000 and Cobas E411 analyzer, respectively. MCV and hemoglobin were measured by Beckman Coulter LH750. Kruskal-Wallis and Mann-Whitney U test were used for comparison between groups. RESULTS: Children (2743 boys, 4567 girls) aged between 1-18 years old were screened. The percentage of iron, folate, vitamin B12 and combined iron and vitamin B12 deficiencies were found to be 21.7%, 8%, 16.9%, and 4.7% respectively. 18.8% of all participants were anemic. The incidence of combined iron and vitamin B12 in anemic group was found to be high (10.2%), although anemic and non-anemic groups were similar with respect to vitamin B12 and folate deficiencies. DISCUSSION AND CONCLUSION: Iron deficiency may mask the megaloblastic anemia caused by vitamin B12 and folate deficiency. Effective preventive social nutrition programs may be useful in preventing anemia.